Competing against COVID-19: what about the mental health problems of athletes with disabilities? - Denerel, N.; Lima, Y. (The Physician and Sportsmedicine, 2022)
Objectives Although there is growing interest in athletes` mental health (MH), there is a paucity of research exploring MH in athletes with disabilities (AWD). The purpose of this study was to evaluate the impact of the COVID-19 pandemic on the psychological state of AWD.